2019
DOI: 10.1007/s00018-019-03398-6
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ-induced metabolic reprogramming during epithelial-to-mesenchymal transition in cancer

Abstract: Metastasis is the most frequent cause of death in cancer patients. Epithelial-to-mesenchymal transition (EMT) is the process in which cells lose epithelial integrity and become motile, a critical step for cancer cell invasion, drug resistance and immune evasion. The transforming growth factor-β (TGFβ) signaling pathway is a major driver of EMT. Increasing evidence demonstrates that metabolic reprogramming is a hallmark of cancer and extensive metabolic changes are observed during EMT. The aim of this review is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(169 citation statements)
references
References 186 publications
(224 reference statements)
5
144
0
Order By: Relevance
“…In summary, our study allowed us to conclude that 21 pathways had similar differences in all three cell lines after induction of EMT ( Figure 1B and Supplementary Tables 1-3). We identified some pathways related to amino acids metabolism, such as alanine, glycine, serine, and glutamate, among others, according to other studies (11,15,17,18). Furthermore, we discovered that additional pathways such as Fatty Acid metabolism, Citric Acid Cycle, and glutathione metabolism also changed after EMT (Supplementary Table 13).…”
Section: Different Nsclc Cell Lines Have Similarities In Metabolic Rementioning
confidence: 88%
“…In summary, our study allowed us to conclude that 21 pathways had similar differences in all three cell lines after induction of EMT ( Figure 1B and Supplementary Tables 1-3). We identified some pathways related to amino acids metabolism, such as alanine, glycine, serine, and glutamate, among others, according to other studies (11,15,17,18). Furthermore, we discovered that additional pathways such as Fatty Acid metabolism, Citric Acid Cycle, and glutathione metabolism also changed after EMT (Supplementary Table 13).…”
Section: Different Nsclc Cell Lines Have Similarities In Metabolic Rementioning
confidence: 88%
“…This result was consistent with our research, suggesting that the EMT process could act as an important regulator during the progression of NSCLC. Since it has been reported that TGF-β signaling could be involved in the EMT process of malignant tumors [41], we will further Figure 5: MiR-188-3p directly targeted NCAPG2. (a) Gene structure of NCAPG2 at the position of 123-130 indicated the predicted target site of miR-188-3p in its 3′UTR, with a sequence of CCCAA.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has proven that TGF-β signaling possesses both Smad and non-Smad pathways, and regulated tumorigenesis via different molecular mechanisms, including, TGF-β1/Smad2/3, PI3K-AKT-mTOR, Wnt, Notch, and ERK, p38, and JUN N-terminal kinase (JNK) MAPK pathways [34][35]. Various studies also indicated that TGF-β was signi cantly associated with the expression of MAGs and metabolic reprogramming of cancer [36][37][38]. Therefore, M2 TAMs secreted TGF-β1 may in uence the metabolic reprogramming in BC by these signaling pathways, especially Smad pathways, to promote the recurrence and progression of BC.…”
Section: Discussionmentioning
confidence: 99%